Profil Farmakologi Binahong (Anredera cordifolia) Sebagai Kandidat Modern Medicine: Tinjauan Sistematis - Vinnie Ayu Fitria; Apriati Kalimatus Sakdiyah; Veni Kurniati; Diky Okta Yudha Putra; Neviaisyah Zevani Putri; Puspa Dwi Pratiwi (Sinteza, 2025)
The pharmacological activity of Binahong has been studied for various therapeutic effects, and the plant is thought to have several bioactive compounds that contribute to its pharmacological activity. This article discusses the pharmacological profile of Anredera cordifolia as a modern medicine candidate. The use of traditional medicine utilizing this plant species has been ongoing since ancient times in Indonesia, a region blessed with abundant flora diversity. This study was examined various medical benefits of the Anredera cordifolia, particularly regarding its antioxidant, antihyperglycemic, antibacterial properties, and wound healing capabilities. The method of this systematic review used the PRISMA framework by searching scientific publications in 2020-2024 through the Crossref database. The research revealed that secondary metabolite compounds in Anredera cordifolia leaf extract include flavonoids, saponins, and phenols, which provide pharmacological effects. Antioxidant capacity measurements using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) technique yielded various IC50 values, indicated its potential as an antioxidant. Additionally, Anredera cordifolia demonstrated significant antihyperglycemic effects in animal experimental models. Its antibacterial activity against various pathogens, along with its ability to accelerate wound healing, further confirms Anredera cordifolia potential as a modern herbal medicine. The conclusion is Anredera cordifolia shows great potential for development as an effective herbal medicine in modern treatment, supporting the trend toward more natural and environmentally friendly alternative medicine.